p21-activated kinase is involved in the sporulation, pathogenicity, and stress response of Arthrobotrys oligospora under the indirect regulation of Rho GTPase-activating protein - Zhu, Meichen; Liu, Yankun; Yang, Xuewei; Zhu, Lirong; Shen, Yanmei; Duan, Shipeng; Yang, Jinkui (Frontiers in Microbiology, 2023)
The p21-GTPase-activated protein kinases (PAKs) participate in signal transduction downstream of Rho GTPases, which are regulated by Rho GTPase-activating proteins (Rho-GAP). Herein, we characterized two orthologous Rho-GAPs (AoRga1 and AoRga2) and two PAKs (AoPak1 and AoPak2) through bioinformatics analysis and reverse genetics in Arthrobotrys oligospora, a typical nematode-trapping (NT) fungus.The transcription analyses performed at different development stages suggested that Aopaks and Aorga1 play a crucial role during sporulation and trap formation, respectively. In addition, we successfully deleted Aopak1 and Aorga1 via the homologous recombination method. The disruption of Aopak1 and Aorga1 caused a remarkable reduction in spore yield and the number of nuclei per cell, but did not affect mycelial growth. In ∆Aopak1 mutants, the trap number was decreased at 48 h after the introduction of nematodes, but nematode predatory efficiency was not affected because the extracellular proteolytic activity was increased. On the contrary, the number of traps in ∆Aorga1 mutants was significantly increased at 36 h and 48 h.In addition, Aopak1 and Aorga1 had different effects on the sensitivity to cell-walldisturbing reagent and oxidant. A yeast two-hybrid assay revealed that AoPak1 and AoRga1 both interacted with AoRac, and AoPak1 also interacted with AoCdc42.Furthermore, the Aopaks were up-regulated in ∆Aorga1 mutants, and Aorga1 was down-regulated in ∆Aopak1 mutants. These results reveal that AoRga1 indirectly regulated AoPAKs by regulating small GTPases.